Review of Multidisciplinary Strategies in the Treatment of Chronic Postoperative Pain. - Zapata Martínez, Irene; García Anaya, María Jesús (Nova Science Publishers, 2022)
Millions of cancer patients are diagnosed each year. Many of these patients require surgical procedures that can cause postoperative pain. Poor postoperative pain control is associated with persistent chronic pain, poor patient satisfaction, increased healthcare costs and psychological consequences. Postoperative pain remains one of the most common challenges following inpatient and outpatient surgery. Oncology patients often present with acute or chronic pain prior to surgery, opioid tolerance or contraindications to some analgesics, making postoperative pain management difficult. In this chapter, we will review some aspects to consider in the management of postoperative pain in the oncological patient.
https://novapublishers.com/open-access/
Keywords: Cáncer - Cirugía; Cuidados postoperatorios; Oncology; Postoperative pain; Cancer